LAWSUIT IN ADMINISTRATIVE COURT AFTER ADMINISTRATIVE PROCEEDINGS BASED ON PERMA NO. 6 OF 2018 - Bimasakti, Muhammad Adiguna (Jurnal Hukum dan Peradilan, 2019)
The enactment of Law No. 30 of 2014 concerning Government Administration very much changes the paradigm of the proceedings in the State Administrative Court. One of the fundamental things is about administrative proceedings as pre-litigation proceedings. Under Article 75 of Law No. 30 of 2014 concerning Government Administration, citizens who feel disadvantaged by a Government’s Decision or Action can file an administrative proceedings, and then file a lawsuit in the Administrative Court. Regarding this regulation, two interpretations arise regarding the obligation of administrative proceedings as pre-litigation proceedings. One party argues that the administrative proceedings as pre-litigation proceedings must be carried out before filing a lawsuit in the Court, and the other argues this is not mandatory. For a period of four years, the interpretation of the obligation of administrative proceedings as a pre-litigation proceedings in Law No. 30 of 2014 concerning Government Administration is floating in the realm of discourse. It was only on December 4th, 2018 that the Supreme Court issued a Supreme Court Regulation (PERMA) No. 6 of 2018 concerning Guidelines for Resolving Disputes Regarding Government Administration After Administrative Proceedings, finally the Supreme Court dictates that administrative proceedings as a pre-litigation proceedings is a must. However, the PERMA does not regulate fundamental things regarding lawsuit after administrative proceedings, namely, who will be seated as the defendant, and what is the object of the lawsuit. In addition, there are also a number of things that needed to be reviewed regarding the arrangements in the PERMA, such as regarding the deadline for a lawsuit in the Court.